Role of Research Methods in Optimization of the Teaching Process - Dautaras, Jonas (Acta Paedagogica Vilnensia, 1993)
The paper presents the survey which was designed to determine the influence of investigatory work of regional studies upon knowledge and independence of the pupils. The study involved 1267 pupils. There was also a teaching experiment, which was attended by 421 pupil. Under the experimental program, the students were primarily introduced to the regional survey activities and the sources of regional studies, extracurricular directions and forms of its research methods, research work, components, etc. After two years of an educational experiment, it became clear that research works have helped achieve better learning results not only in history and geography, but also other subjects. Students began to prepare homework and school assignments in a shorter period of time as research method helps to gain knowledge from a variety of sources of information, teaches a variety of learning methods, forms research skills, promotes creativity and logical thinking, diligence, raises motivation.